(untitled) (PerCursos, 2023)
Knowing the serum levels of 25(OH)D and the bone profile of old women is relevant for the maintenance of physical and functional independence. Objective: To evaluate 25(OH)D supplementation in physically active old women. Methods: Intervention trial in groups. A total of 348 elderly women aged ≥ 60 years (67±5 years), practicing physical exercise for at least one year, at the Sesc Santana - Social Service of Commerce of São Paulo (SP) were evaluated. We compared 146 practitioners of Aquatic training (AT); 99 old women who practiced Multifunctional Gymnastics (GMF); and 103 old women who did not practice supervised physical exercise, who were classified as sedentary (SED). The old women with 25(OH)D levels below the median of the respective group were supplemented with cholecalciferol, 21,000 IU/week, for 12 months. Serum dosage of 25(OH)D, calculation of Body Mass Index (BMI) and Bone Densitometry (Dexa) were performed. The comparison of baseline data was performed using the univariate General Linear Model (GLM) and for the time of supplementation, the GLM for repeated measures, considering the significance level α<0.005. Results: Supplementation significantly increased 25(OH)D levels in AT (12.06±2.64 - 39.42±13.82 ng/mL - p<0.001), GMF (13.01±3.43 - 37.36±10.46 ng/mL - p<0.001) and SED (10.86±2.26 ng/mL - 38.30±13.77 ng/mL - p<0.001). There were no significant differences on the bone profile. Conclusion: The old women in the groups, even physically independent, presented osteopenia, osteoporosis and 25(OH)D deficiency, which was corrected after the supplementation protocol, showing its effectiveness.